PENGARUH PENGELOLAAN KEUANGAN DAERAH DAN PENGAWASAN INTERNAL TERHADAP KINERJA PEMERINTAH (Studi Kasus Pada Satuan Kerja Perangkat Daerah Kota Semarang) - Dea Rahma Novitasari; Tri Jatmiko Wahyu Prabowo (Diponegoro Journal of Accounting, 2020)
This study aims to obtain empirical evidence regarding the implementation of regional financial management supervision in the Semarang City Regional Work Unit (SKPD), both partially and simultaneously totaling 46 SKPD. The population in this study is the Semarang City Regional Performance Unit. Source of data used for the research is primary data which is quantitative research obtained from questionnaires and using the saturated technique. Analysis of the data in this study uses descriptive statistical analysis, classic assumption tests, and multiple linear regression. The result of the analysis of the study shows that internal control and regional financial management had a positive and significant effect on the performance of local governments.